Chapter La cartografia italiana al tempo di Leonardo. Fra cultura umanistica e progetto territoriale - Rombai, Leonardo (Territori, 2023)
The essay studies the maps produced in the 15th and early 16th centuries by Venice and other states with reference to water management, exploitation of agricultural resources, administrative organization, border control and war strategies. It also considers the extraordinary maps of Southern Italy produced by the Aragonese government between the fifteenth and sixteenth centuries (known only thanks to their 18th-century copies), which bring out a grandiose and organic general plan of topographic survey by compass and astronomical observations.